Extraction of Pectin from Cui Lemon (Citrus microcarpa) and Its Application in Pineapple Jam - Rompas, Veckie Frankie; Mamuaja, Christine F.; Suryanto, Edi (Jurnal Ilmu dan Teknologi Pangan, 2016)
Cui lemon (Citrus microcarpa Bunge) is a type of small citrus variety that is widely available in North Sulawesi. It is very popular as a preservative and deodorizing agent of fishy odor in fish products, and it is used in traditional chilly sauce "Dabu-Dabu" with a very distinctive aroma arouse your appetite. Lemon cui contains vitamin C and phenolic compounds. Lemon is an important economic value and is rich in antioxidant phytochemicals particularly high content of vitamin C. The objectives of this study were to examine the effect of temperature, and extration time on the pectin yield, and examine the effect of lemon pectin addition on panelist preference of pineapple jam. The pectin in the sample was extracted at different temperatures, namely  70, 80, 90 and 100 0C with 60 and 80 minutes extraction time, then the pectin was applied in the processing of pineapple jam.  The pectin extraction was carried out in the following procedures. The experiment was arranged in completely randomized design (CRD) in factorial experiment.  The jam products were calculated and analyzed forAnalysis conducted for pectin yield, methoxyl, moisture, and ash contents.  The data by were analyzed using analysis of variance (ANOVA) and followed by LSD test if the anova was significant. The results showed that temperature affected yield of extraction of pectin  significantly (P<0.05) whereas time had no effect (P>0.05). Addition of 1% pectin in pineapple jam significantly affected (P<0.05) the aroma and texture,but were not for color and the taste (P>0.05). The panelist test on pineapple jam showed that, in average, the panelists liked the addition of pectin treatment for parameter of aroma and texture, but for the color and taste parameters panelists give a neutral assessment. Extraction at a temperature of 100 0C for 80 minutes resulted in optimal pectin yield (3.74%) with methoxyl, moisture, and ash contents of 12.66%, 10.37%, 1.63%, respectively.%. Keywords: lemon cui, extraction, pectin, methoxyl, pineapple jams